The Association Between Comorbidities and Severity of Dengue Among Adults in Lombok - Khairifathiyyah Khairifathiyyah; Indah Sapta Wardani; Philip Habib; Dewi Suryani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Dengue remains a major public health concern in Indonesia, particularly in Lombok, West Nusa Tenggara, where evidence on the association between comorbidities and dengue severity is limited. This study aimed to assess the relationship between comorbidities and dengue severity among adults in Lombok. A retrospective cross-sectional study was conducted using medical records of adult dengue patients treated at West Nusa Tenggara Province General Hospital between 2023 and 2024. Fisher’s exact test was used for statistical analysis. A total of 154 patients were included, comprising 66 patients with comorbidities and 88 without comorbidities. Gastrointestinal and hepatobiliary diseases were the predominant organ-system comorbidity category, while pneumonia and type 2 diabetes mellitus were the most common individual comorbidities. No significant association was found between comorbidities and dengue severity (p > 0.05). However, the findings should be interpreted cautiously due to unequal distribution of severity categories and limited number of dengue shock syndrome cases. In conclusion, no significant association was observed between comorbidities and dengue severity among adult patients in Lombok. Future multicenter studies with larger and more balanced samples are needed to investigate determinants of dengue severity. Additional clinical, immunological, and virological factors should be evaluated to improve risk stratification and patient management.